Group Discussion Based on Podcast and to Improve English Listening Skill to ESL Learners - Ervita C Tania; Maniku Jein (Journal of English Language Teaching, Linguistics, and Literature Studies, 2022)
Group Discussion Based on Podcast and to Improve English Listening Skill to ESLLearners. This study is focused on group discussion based on podcast to improveEnglish listening skill to ESL learners above fourteen (14) years old English learners inBethany Family Church, Bitung city. This study uses a quantitative method with a preexperimentaldesign by applying one pre-test and post-test design. The writer uses pretestand post-test as instruments. Data were analyzed statistically by using t-test. Theresults of this study indicate that podcasts and group discussion are effective inteaching listening comprehension to ESL English learners in Bethany Family Church,Bitung city. This can be seen from the results of the t-test, the significance and progressof the learners? scores on the post-test from the pre-test. The mean of pre-test scorewas 7,25 and the average post-test score was 8,625. This indicates a significant increasein the mean scores between the learners' pre-test and post-test. The results of thisstudy are expected to be useful for teachers, and learners to enrich their reference inteaching and learning English Listening.Keywords: Group Discussion Based on Podcast; ESL Learners